2014
DOI: 10.1002/joc.4153
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic influence on summer precipitation trends over South America in CMIP5 models

Abstract: Austral summer rainfall trends are analysed over South America from observations and simulations of the Coupled Model Intercomparison Project version 5 between 1902 and 2005. Positive trends in southeastern South America (SESA) and negative ones in the southern Andes (SAn) are the most significant observed features. Mean trends obtained from an ensemble of 59 simulations from 14 models for the historical experiment (including both natural and anthropogenic forcings) are able to reproduce those precipitation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
66
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 13 publications
11
66
0
1
Order By: Relevance
“…The pattern is very similar to that obtained by Vera and Díaz () for a set of 14 CMIP5 models. However, as those authors pointed out, simulated trends are weaker and located westward than those obtained using GPCC data (Figure of Vera and Díaz, ). The associated inter‐model dispersion (Figure (b)) is larger at the tropics.…”
Section: Eof1 Activity and Rainfall Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pattern is very similar to that obtained by Vera and Díaz () for a set of 14 CMIP5 models. However, as those authors pointed out, simulated trends are weaker and located westward than those obtained using GPCC data (Figure of Vera and Díaz, ). The associated inter‐model dispersion (Figure (b)) is larger at the tropics.…”
Section: Eof1 Activity and Rainfall Trendsmentioning
confidence: 99%
“…The rainfall linear trend resulted from the MEM_A (Figure (a)) exhibits significant values extended over central‐northern Argentina, southern Brazil and Uruguay. The pattern is very similar to that obtained by Vera and Díaz () for a set of 14 CMIP5 models. However, as those authors pointed out, simulated trends are weaker and located westward than those obtained using GPCC data (Figure of Vera and Díaz, ).…”
Section: Eof1 Activity and Rainfall Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seven individual models do present a trend, but it is smaller than that in the observations. As mention above, most of the historical simulations of the CMIP5 models can recognize the right sign of the summer precipitation changes in southeastern South America, although weaker than observed (Vera and Díaz, ). Our results suggest that the annual and summer mean trend in precipitation are weakly simulated also in the northeast region of Argentina.…”
Section: Historical Long‐term Simulationsmentioning
confidence: 99%
“…However, they concluded that it was difficult to draw a connection between those signatures and the ENSO signal. More recently, Vera and Díaz (2014) used CMIP5 simulations to provide significant evidence that precipitation changes observed in SESA over the last century are at least partially explained by the human-induced greenhouse gases increment. Conclusions from these studies point the need for further investigations to discern whether 20th century hydroclimatic changes in SESA are influenced by forcing from SST anomalies and/or from anthropogenic forcing (i.e., human-induced climate change).…”
Section: Introductionmentioning
confidence: 99%